Folic acid supplementation and prevention of chronic kidney disease. Issue 9 (September 2017) - Farnell, Edwin
Abstract : N/A: Xu X, Qin X, Li Y, Sun D, Wang J, Liang M, et al. Efficacy of folic acid therapy on the progression of chronic kidney disease: The renal substudy of the China Stroke Primary Prevention Trial. JAMA Intern Med . 2016; 176(10):1443–1450.